2017
DOI: 10.1098/rspb.2016.2592
|View full text |Cite
|
Sign up to set email alerts
|

Egg discrimination along a gradient of natural variation in eggshell coloration

Abstract: Accurate recognition of salient cues is critical for adaptive responses, but the underlying sensory and cognitive processes are often poorly understood. For example, hosts of avian brood parasites have long been assumed to reject foreign eggs from their nests based on the total degree of dissimilarity in colour to their own eggs, regardless of the foreign eggs' colours. We tested hosts' responses to gradients of natural (blue-green to brown) and artificial (green to purple) egg colours, and demonstrate that ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 68 publications
8
101
0
Order By: Relevance
“…Hanley et al. () demonstrated robins’ rejection decisions are fine‐tuned to the gradient of natural egg colors, but robins ignore perceivable differences along artificial color gradients, a finding inconsistent with the internal “own egg versus foreign egg” template (or multiple threshold, sensu Hanley et al., ) hypothesis. Similarly, Dainson, Hauber, López, Grim, and Hanley () also found that robin egg rejection responses to egg spot coloration are likely tuned to a gradient of natural egg color patterns, where robins are more inclined to reject model eggs that have highly contrasting brown spots against a mimetic blue‐green robin egg background color.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hanley et al. () demonstrated robins’ rejection decisions are fine‐tuned to the gradient of natural egg colors, but robins ignore perceivable differences along artificial color gradients, a finding inconsistent with the internal “own egg versus foreign egg” template (or multiple threshold, sensu Hanley et al., ) hypothesis. Similarly, Dainson, Hauber, López, Grim, and Hanley () also found that robin egg rejection responses to egg spot coloration are likely tuned to a gradient of natural egg color patterns, where robins are more inclined to reject model eggs that have highly contrasting brown spots against a mimetic blue‐green robin egg background color.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we confirmed that discrete, categorical differences in egg background color, maculation, and size are all important cues for foreign egg recognition in robins. However, recent experimental approaches have set a new standard, using model eggs, which vary continuously rather than discretely, along natural gradients of different background colors (Hanley et al., ), as well as maculation patterns and contrasts (Dainson et al., ), and sizes and shapes (Igic et al., ). Egg rejection studies performed with continuously varying model eggs, in combination with avian visual modeling (Avilés, ; Cassey et al., ; Spottiswoode & Stevens, ), allow for estimation of perceivable differences to the host species of interest for each model egg feature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that hosts set thresholds along phenotypic extrema on each side of a phenotypic range ('multiple thresholds'), in this case, eggs that are very blue -green and brown. However, a recent study [17] on two species of thrushes (Turdus spp.) found that this was not the case.…”
Section: Introductionmentioning
confidence: 99%